1997
DOI: 10.1080/004982597239921
|View full text |Cite
|
Sign up to set email alerts
|

Induction of CYP3A isoforms in cultured precisioncut human liver slices

Abstract: 1. The effect of rifampicin on cytochrome P450 isoforms in the CYP1A and CYP3A subfamilies has been studied in 72-h cultured precision-cut human liver slices. 2. In cultured human liver slices 50 microM rifampicin induced testosterone 6 beta-hydroxylase activity, but had no effect on 7-ethoxyresorufin O-deethylase and 7-methoxyresorufin O-demethylase activities. 3. Western immunoblotting of liver slice microsomes was performed with antibodies to rat CYP1A2 and human CYP3A4. Compared with control (dimethyl sulp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
14
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 36 publications
(14 citation statements)
references
References 14 publications
0
14
0
Order By: Relevance
“…The concentrations of BNF, DEX, LANS, NaPB, and RIF were selected from previous in vitro studies in either human hepatocytes (Curi-Pedrosa et al, 1994;Donato et al, 1995;Meunier et al, 2000;Sahi et al, 2000) or liver slices (Lake et al, , 1997. For MCP, a rodent peroxisome proliferator and CYP4A inducer, the concentration selected was based on that used in previous studies with cultured rat and human liver slices (Beamand et al, 1993;Lake et al, 1996).…”
Section: P450 Induction In Human Liver Slicesmentioning
confidence: 99%
See 3 more Smart Citations
“…The concentrations of BNF, DEX, LANS, NaPB, and RIF were selected from previous in vitro studies in either human hepatocytes (Curi-Pedrosa et al, 1994;Donato et al, 1995;Meunier et al, 2000;Sahi et al, 2000) or liver slices (Lake et al, , 1997. For MCP, a rodent peroxisome proliferator and CYP4A inducer, the concentration selected was based on that used in previous studies with cultured rat and human liver slices (Beamand et al, 1993;Lake et al, 1996).…”
Section: P450 Induction In Human Liver Slicesmentioning
confidence: 99%
“…For example, Aroclor 1254, ␤-naphthoflavone (BNF), 3,3Ј-diindolylmethane, omeprazole, and 2,3,7,8-tetrachlorodibenzo-p-dioxin have been reported to induce CYP1A enzymes in cultured human liver slices (Lake et al, , 1998Olson et al, 1997;Drahushuk et al, 1998;Glöckner et al, 1999). In one study rifampicin (RIF) was reported to induce CYP3A4 (Lake et al, 1997), and in a recently published abstract, cyclophosphamide and phenobarbital were reported to induce CYP2B6 and CYP3A4 in cultured human liver slices (Martin et al, 2002).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…In the past decade, precision-cut liver slices have been successfully used as an in vitro model for biotransformation (Dogterom and Rothuizen, 1993;Ball et al, 1996;Hashemi et al, 1999), hepatotoxicity (Wormser et al, 1990;Miller et al, 1993), and enzyme induction studies (Lake et al, 1997) in a variety of animal species. Important determinants in this successful application of liver slices are undoubtedly the maintenance of normal tissue architecture, cell heterogeneity, and cell-cell communications within the livers' original tissue matrix.…”
mentioning
confidence: 99%